Application of DWT and fuzzy logic algorithm for classifying simultaneous fault types - Pothisarn, C.; Ngaopitakkul, A. (My University, 2011)
This paper proposes a technique using discrete wavelet transform (DWT) and fuzzy logic for identifying types of simultaneous fault along the transmission systems. The PSCAD/EMTDC is used to simulate fault signals. The mother wavelet daubechies4 (db4) is employed to decompose high frequency component from these signals. The coefficients detail (phase A, B, C and zero sequence of post-fault current signals) of DWT at the first peak time that positive sequence current can detect fault, is performed as input variables for the proposed algorithm. The result shows that the proposed technique gives satisfactory accuracy, and will be very useful in the development of a power system protection scheme. © 2011 IEEE.
Keywords: ATP/EMTP; discrete wavelet transform; Fault Types; fuzzy logic; Simultaneous Fault